Penentuan Nilai SPF (Sun Protection Factor) Limbah Destilasi Rimpang Jahe Emprit (Zingiber officinale Var Amarum) dengan Metode Spektrofotometri UV-VIS - Nila Ulliyatun Nur Syarofa; Berliansyah Rahmadani Putrianto; Tarisa Martha Sari; Bima Tutus Widiyanto; Selly Agustina; Ulvi Rohmawati; Diyan Sakti Purwanto (Pusat Riset dan Inovasi Nasional, 2025)
Zingiber officinale Var. Amarum (commonly known as jahe emprit) is a local ginger variety recognized for its richness in bioactive compounds, including flavonoids, phenolics, tannins, saponins, and terpenoids, which are widely reported to possess antioxidant properties and the ability to absorb ultraviolet (UV) radiation. These characteristics highlight its potential as a natural source of photoprotective agents. The present study was conducted to evaluate the Sun Protection Factor (SPF) of ginger rhizome distillation waste and to perform phytochemical screening in order to identify its secondary metabolite content. Distillation was performed on 250 grams of fresh ginger rhizomes using a solvent ratio of 1:2 (b/v). The process yielded 130 mL of liquid waste with a 52% recovery rate and retained the distinctive aromatic profile of ginger. Phytochemical analysis revealed the presence of flavonoids, phenolics, saponins, and phytosterols, while alkaloids were detected only in trace amounts, suggesting the waste still contains valuable bioactive constituents despite undergoing distillation. Determination of SPF was carried out using the Mansur spectrophotometric method, which measures absorbance within the wavelength range of 290–320 nm at 5 nm intervals. The extract demonstrated an average SPF value of 39.29, which is categorized as ultra protection, indicating a very high level of photoprotective capacity. These results confirm that ginger rhizome distillation waste retains compounds with strong UV absorption and antioxidant potential, supporting its use as an active ingredient in sunscreen formulations. Beyond its functional efficacy, the utilization of this by-product also promotes sustainability by reducing waste from the essential oil industry and contributing to eco-friendly cosmetic innovation. In conclusion, the study provides scientific evidence that ginger distillation waste can be valorized into high-value products, offering both environmental and economic benefits while meeting the growing demand for natural and safe alternatives in skincare formulations.